A Literature Review of Localized Mediastinal Mesothelioma and a Rare Case Report - Xiao, Qiang Meng; Zhang, Meng; du, Fengjun; Peng, Hui; Chen, Jun; Liu, Hailong (Asian Pacific Journal of Cancer Care, 2021)
Background: Primary localized mediastinal mesothelioma is a rare tumour which accounts for about 0.7% of all mesotheliomas. The mesothelial cells lining of the pericardium are suggested as the most probable cells of origin. Mediastinal pleural mesothelioma are distinctly uncommon, which has only been reported in a single case. Case presentation: We report a case of a 57 years old man with primary mediastinal pleural mesothelioma involving middle and posterior upper mediastinum, one months following surgery, the patient is alive with good performance status. Chest plain scan and contrast-enhanced computer tomography（CT）scan showed a 43 mm×36 mm×36 mm tumor，with a CT value of about 41.5 HU, an arterial phase CT value of about 59.8HU and a venous phase CT value of about 77.5HU during the contrast-contrast-enhanced scan.Patients underwent thoracotomy.The pathological diagnosis was derived from malignant pleural mesothelioma(MPM) growing from the chest wall into the mediastinum. Conclusions Imaging manifestations of tumors have rarely been described in the literature. A short review of literature on MPM is given and summarize the imaging characteristics.